Chronic rapamycin treatment decreases hepatic IL‐6 protein, but increases autophagy markers as a protective effect against the overtraining‐induced tissue damage. (23rd June 2022) - Pinto, Ana P.; da Rocha, Alisson L.; Marafon, Bruno B.; Nogueira, Jonatas E.; Branco, Luiz G. S.; Pauli, José R.; de Moura, Leandro P.; Cintra, Dennys E.; Ropelle, Eduardo R.; da Silva, Adelino S. R.
Abstract: Regular endurance exercise is a non‐pharmacological strategy to protect the liver against diseases. Conversely, exercise may be harmful when excessive, the so‐called overtraining. As expected, mice who underwent an overtraining protocol presented higher levels of proinflammatory cytokines in the serum and liver. Based on the relationship among overtraining, inflammation and mammalian target of rapamycin complex 1 (mTORC1) upregulation, the present study verified if animals submitted to an overtraining protocol, but with inhibition of the mTOR pathway via rapamycin injections could mitigate the liver and serum inflammation. Once autophagy can be linked to the improvement of hepatic dysfunction, we also investigated if the inhibition of mTORC1 by rapamycin can improve hepatic autophagy. The animals were randomized into four groups: control (CT; sedentary mice), overtraining by downhill running (OT; mice submitted to the downhill running‐based overtraining protocol), overtraining by downhill running with chronic administration of rapamycin (OT/Rapa; mice submitted to the downhill running‐based overtraining protocol with intraperitoneal injections of rapamycin) and aerobic (AER; submitted to aerobic training protocol). The serum and liver of the animals were used for biochemical analysis, reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR) and immunoblotting. The main results are (a) OT and OT/Rapa protocols decreased the performance; (b) the protein levels of interleukin 6 (IL‐6) were higher for the OT group; the OT/Rapa group reduced the autophagic genes, increased the microtubule‐associated protein light chain 3 II/I (LC3II/LC3I) protein ratio and decreased the sequestosome 1 (SQSTM1) protein. In conclusion, rapamycin appears efficiently to increase the autophagy proteins and decrease IL‐6 protein in the liver of overtraining mice.